FRI0199 Rituximab in Combination with Leflunomide: Results from A Multicenter Randomized Placebo Controlled Investigator Initiated Clinical Trial in Active Rheumatoid Arthritis (Amara-Study). (15th July 2016) - Behrens, F.; Rossmanith, T.; Köhm, M.; Alten, R.; Aringer, M.; Backhaus, M.; Baerwald, C.; Burmester, G.; Feist, E.; Kellner, H.; Krüger, K.; Müller-Ladner, U.; et al.
Abstract : Background: Use of biologicals such as Rituximab (RTX) in Rheumatoid Arthritis (RA) is effective and often only licensed in combination with Methotrexate (MTX). In cases of contraindications to or intolerances, other cDMARDs are frequently used in routine care without data from RCTs. Objectives: To demonstrate safety and efficacy of RTX in combination with Leflunomide (LEF) in a multicenter randomized placebo (PLA) controlled clinical trial in Germany. Methods: A total of 189 patients with active RA (DAS28 >3.2 and at least 3 SJC and 3 TJC) despite stable LEF treatment were screened for a 52-weeks double-blind placebo controlled multicenter RCT. Patients were randomized to receive either two times 1000mg RTX i.v. or PLA, followed by a second course of RTX of either two times 500 or 1000 mg at week 24. The primary endpoint of the study was superiority of RTX in ACR20 and 50 responses vs. PLA during 24-weeks treatment period. Adult patients who had inadequate response to more than one antiTNF or failed more than three cDMARDs were excluded. Disease activity as well as patient reported outcomes were measured at each visit. For safety evaluation, frequency and severity of adverse events were documented. Results: Of 189 screened patients 148 were randomized. The mean age was 56 years; the mean body weight 76 kg and 74% were female. The disease activity (DAS28) at baseline was 5.57 for RTX and 5.54 in the PLA group. All baseline-characteristics were well balanced between the treatment arms. RTX demonstrated significant superiority compared to PLA at week 16 in both, ACR 20 and ACR 50 response. ACR 20 response was significant superior for RTX treatment at weeks 12, 16 and 24 in both analyses, per protocol and modified intention to treat (see table). DAS28 levels in the RTX treatment-group decreased to 3.69 at week 24 (PLA 4.51) and to 3.01 at week 52. A total of 372 adverse events (AE) were observed during the one-year study period, only 14 were classified as severe (10 in RTX and 4 in PLA). 43 serious adverse events were reported, 28 of them in the RTX treatment group during the placebo controlled period. Conclusions: Here we report for the first time data of a RCT of combination of RTX with LEF. The treatment with RTX in combination with LEF demonstrated significant efficacy compared to the PLA for ACR20 response and for ACR50 response as well as reduction in DAS28. The highest level of response was seen at week 16. The combination of RTX and LEF demonstrated a reasonable safety profile. Disclosure of Interest: F. Behrens Grant/research support from: Roche, T. Rossmanith: None declared, M. Köhm: None declared, R. Alten Grant/research support from: Roche, M. Aringer Grant/research support from: Roche, M. Backhaus Grant/research support from: Roche, C. Baerwald Grant/research support from: Roche, G. Burmester Grant/research support from: Roche, E. Feist Grant/research support from: Roche, H. Kellner Grant/research support from: Roche, K. Krüger Grant/research support from: Roche, U. Müller-Ladner Grant/research support from: Roche, A. Rubbert-Roth Grant/research support from: Roche, H.-P. Tony Grant/research support from: Roche, S. Wassenberg Grant/research support from: Roche, H. Burkhardt Grant/research support from: Roche